Videos in Short-Video Sharing Platforms as Sources of Information on Colorectal Polyps: Cross-Sectional Content Analysis Study - Jia-Lun Guan; Su-Hong Xia; Kai Zhao; Li-Na Feng; Ying-Ying Han; Ji-Yan Li; Jia-Zhi Liao; Pei-Yuan Li (JMIR Publications, 2024)
BackgroundShort videos have demonstrated huge potential in disseminating health information in recent years. However, to our knowledge, no study has examined information about colorectal polyps on short-video sharing platforms. ObjectiveThis study aimed to analyze the content and quality of colorectal polyps-related videos on short-video sharing platforms. MethodsThe terms "肠息肉" (intestinal polyps) or "结肠息肉" (colonic polyps) or "直肠息肉" (rectal polyps) or "结直肠息肉" (colorectal polyps) or "大肠息肉" (polyps of large intestine) were used to search in TikTok (ByteDance), WeChat (Tencent Holdings Limited), and Xiaohongshu (Xingyin Information Technology Limited) between May 26 and June 8, 2024, and then the top 100 videos for each search term on different platforms were included and recorded. The Journal of American Medical Association (JAMA) score, the Global Quality Scale (GQS), the modified DISCERN, and the Patient Education Materials Assessment Tool (PEMAT) were used to evaluate the content and quality of selected videos by 2 independent researchers. SPSS (version 22.0; IBM Corp) and GraphPad Prism (version 9.0; Dotmatics) were used for analyzing the data. Descriptive statistics were generated, and the differences between groups were compared. Spearman correlation analysis was used to evaluate the relationship between quantitative variables. ResultsA total of 816 eligible videos were included for further analysis, which mainly conveyed disease-related knowledge (n=635, 77.8%). Most videos were uploaded by physicians (n=709, 86.9%). These videos had an average JAMA score of 2.0 (SD 0.6), GQS score of 2.5 (SD 0.8), modified DISCERN score of 2.5 (SD 0.8), understandability of 80.4% (SD 15.6%), and actionability of 42.2% (SD 36.1%). Videos uploaded by news agencies were of higher quality and received more likes and comments (all P<.05). The number of collections and shares of videos about posttreatment caveats were more than those for other content (P=.03 and P=.006). There was a positive correlation between the number of likes, comments, collections, and shares (all P<.001). The duration and the number of fans were positively correlated with the quality of videos (all P<.05). ConclusionsThere are numerous videos about colorectal polyps on short-video sharing platforms, but the reliability and quality of these videos are not good enough and need to be improved.